Effect of Weight Loss on Postprandial Lipaemia and Low-Density Lipoprotein Receptor Binding in Overweight Men - James, Anthony; Watts, G.; Barrett, H.; Smith, D.; Pal, Sebely; Chan, D.; Mamo, John (W.B. Saunders Co., 2003)
Obestity is associated with a range of metabolic abnormalities including fasting and postprandial dyslipidemia, both of which may contribute to increased atherosclerotic risk. Male obese subjects have a decreased level of low-density lipoprotein (LDL) receptor binding in mononuclear cells, the level of which reflects binding in the liver, compared with lean controls. In this study, we investigated whether the implementation of a weight loss regimen in viscerally obese subjects improves LDL receptor binding level. We examined apolipoprotein B48 (apo B48) and retinyl palmitate (RP) metabolism following an oral fat challenge to determine whether weight loss improves postprandial dyslipidemia in viscerally obese subjects. Male obese, mildly dyslipidemic, and insulin-resistant subjects were randomly assigned to either a weight loss (n = 12) or control weight maintenance (n = 10) group. In response to weight loss of 10 kg, insulin sensitivity improved as evidenced by decreased fasting insulin and homeostatic model assessment (HOMA) score. In addition, LDL receptor binding in mononuclear cells increased significantly by 27.5% and LDL-cholesterol was significantly reduced. However, despite the increased LDL receptor levels, fasting apo B48 levels did not fall. Postprandially, the area under the curve (AUC) for RP was significantly reduced after weight loss, but the incremental and total AUCs for apo B48 were not altered. Apo B48 is an unequivocal marker of chylomicron particle number; hence, the reduction in RP metabolism achieved with weight reduction may reflect decreased lipid incorporation into nascent chylomicrons or improved hydrolysis of triglyceride-rich chylomicrons resulting from a decreased competition with hepatic lipoproteins for lipoprotein lipase. Our findings suggest that the improvement in LDL receptor binding following weight reduction of 10 kg in insulin-resistant male obese subjects is insufficient to reduce the elevated chylomicron remnant levels.